Root ZX Electronic Foramen Locator: An Ex Vivo Study of Its Three Models’ Precision and Reproducibility - Bernardo Almeida Aguiar; Rafael Santos Reinaldo; Luciana Maria Arcanjo Frota; Mônica Sampaio do Vale; Bruno Carvalho de Vasconcelos (International Journal of Dentistry)
Although Root ZX is considered the gold standard electronic foramen locator (EFL), two variations of this device were launched, however without different operating mechanisms. This investigation aims to evaluate the precision of Root ZX (RZX), Root ZX II (RII), and Root ZX Mini (RM) EFLs. After access cavity preparation, 32 mandibular single rooted human premolars had their real length measured with the aid of a #15 K-type manual file under magnification (25x). Electronic measurements were performed by the devices in an alternate order until the apical foramen was reached (0.0). Each measurement was performed with adjusted file to the real length of the teeth and verified with a digital caliper. The accuracy of the EFLs was 68.8% (RZX), 65.8% (RII), and 68.8% (RM), considering ±0.5 mm as a margin of tolerance. The mean errors of the devices were 0.37±0.25 mm (RZX), 0.41±0.34 mm (RII), and 0.32±0.28 mm (RM). ANOVA and Tukey test were applied to analyze the obtained data, which showed that there were no statistically significant differences among the locators (P>.05). It can be concluded that the three tested devices demonstrated precise measurements of the real length of the canal without performance differences among them.